ANALISIS CITRA LUXURY BRAND YSL BEAUTY INDONESIA DALAM KONTEN TIKTOK @YSLBEAUTY_INDONESIA - Ishma Syahirah, Dwita Safitri; Mustika Chairil, Augustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines how YSL Beauty Indonesia constructs it’s luxury brand image on TikTok, a platform known for mass accessibility, which contrats with the exclusive nature of luxury brands. Using a qualitative content analysis method by Klaus Krppendorff, this study analyzez 15 selected video from the @yslbeauty_indonesia account. The analysis employs Jean Noel Kapferer Brand Identity Prism to identity pillars and Jennifer Aaker’s Brand Personality dimensions to interpret brand character. The findings reveal that YSL Beauty maintains it’s exclusivity not through aggressive hard selling, but by consistently presenting cinematic aesthetics dominated by iconic black and gold colors, and narratives rooted “freedom” and “heritage” Le Smoking. YSL successfully translates it’s french Haute Couture Identity into digital characterictics specifically Sophistication, Competence, and Ruggedness positioning the brand as an aspirational lifesyle mentor. This research validates that luxury brand images on TikTok are constructed through a sctructured communication strategy that ntegrates heritage, visual consistency, and a strong, independent brand personality, thereby maintaining prestige despite the open nature of the TikTok platform.